Association of Preadmission Statin Use and Mortality in Critically Ill Patients: A Meta-Analysis of Cohort Studies - Yu, Shao-shuo; Jin, Jian; Yao, Ren-qi; Wang, Bo-li; Hu, Lun-yang; Wu, Guo-sheng; Sun, Yu (Frontiers in Medicine, 2021)
Background: A large number of studies have been conducted to determine whether there is an association between preadmission statin use and improvement in outcomes following critical illness, but the conclusions are quite inconsistent. Therefore, this meta-analysis aims to include the present relevant PSM researches to examine the association of preadmission use of statins with the mortality of critically ill patients. Methods: The PubMed, Web of Science, Embase electronic databases and printed resources were searched for English articles published before March 6, 2020 on the association between preadmission statin use and mortality in critically ill patients. The included articles were analyzed in RevMan 5.3. The Newcastle-Ottawa Scale (NOS) was used to conduct quality evaluation, and random/fixed effects modelling was used to calculate the pooled ORs and 95% CIs. We also conducted subgroup analysis by outcome indicators (30-day, 90-day, hospital mortality). Results: All 6 PSM observational studies were assessed as having a low risk of bias according to the NOS. For primary outcome—overall mortality, the pooled OR (preadmission statins use vs. no use) across the 6 included studies was 0.86 (95% CI, 0.76–0.97; P=0.02). For secondary outcome—use of mechanical ventilation, the pooled OR was 0.94 (95% CI, 0.91–0.97; P=0.0005). The corresponding pooled ORs were 0.67 (95% CI, 0.43–1.05; P=0.08), 0.91 (95% CI, 0.83–1.01; P=0.07) and 0.86 (95% CI, 0.83–0.89; P<0.00001) for 30-day, 90-day and hospital mortality, respectively. Conclusions: Preadmission statin use is associated with beneficial outcomes in critical ill patients, indicating a lower short-term mortality, less use of mechanical ventilation and an improvement in hospital survival. Further high-quality original studies or more scientific methods are needed to draw a definitive conclusion.